The hormonal Zeitgeber melatonin: role as a circadian modulator in memory processing - Rawashdeh, Oliver; Maronde, Erik (Frontiers in Molecular Neuroscience, 2012)
The neuroendocrine substance melatonin is a hormone synthesized rhythmically by the pineal gland under the influence of the circadian system and alternating light/dark cycles. Melatonin has been shown to have broad applications, and consequently becoming a molecule of great controversy. Undoubtedly, however, melatonin plays an important role as a time cue for the endogenous circadian system. This review focuses on melatonin as a regulator in the circadian modulation of memory processing. Memory processes (acquisition, consolidation and retrieval) are modulated by the circadian system. However, the mechanism by which the biological clock is rhythmically influencing cognitive processes remains unknown. We also discuss, how the circadian system by generating cycling melatonin levels can implant information about daytime into memory processing, depicted as day and nighttime differences in acquisition, memory consolidation and/or retrieval.